Hepatitis B Virus X Protein Stimulates Proliferation, Wound Closure and Inhibits Apoptosis of HuH-7 Cells via CDC42 - Xu, Yongru (Int J Mol Sci, 2017)
Chronic hepatitis B virus (HBV) infection has been considered as the major cause of hepatocellular carcinoma (HCC). Hepatitis B virus X protein (HBx) has been reported to be oncogenic. The underlying mechanisms of HBV-related HCC are not fully understood, and the role played by the HBx protein in HBV induced carcinogenesis remains controversial. CDC42, a member of the Rho GTPase family, has been reported to be overexpressed in several different cancers, including HBV-related HCC. However, the specific role of CDC42 in HCC development remains unclear. Here, we investigated the cellular mechanisms by which CDC42 was responsible for the higher proliferation of HuH-7 cells mediated by HBx. We found that the expression level of CDC42 and its activity were significantly increased in HuH-7-HBx cells. The deficiency of CDC42 using the CRISPR/Cas9 system and inhibition by specific inhibitor CASIN led to the reduction of HBx-mediated proliferation. Furthermore, we observed that IQ Motif Containing GTPase Activating Protein 1 (IQGAP1), the downstream mediator of the CDC42 pathway, might be involved in the carcinogenesis induced by HBx. Therefore, the HBx/CDC42/IQGAP1 signaling pathway may potentially play an important role in HBx-mediated carcinogenesis.